The PENINGKATAN HASIL PUPUK KOMPOS KELOMPOK TANI DENGAN MENGAPLIKASIKAN SIMOSTI DAN MARKETPLACE - Sihombing, Panangian; Sr, Masdania Zurairah; Rafiqah Humaira (Jurnal Abdi Insani, 2024)
Micro, small and medium business actors who are members of the This activity aims to empower the Pondok Miri Asri Farmers Group by applying an Internet of Things-integrated compost monitoring system (Simosti) and marketplace technology. Problems in the production sector include the quality of the production results, namely, the compost fertilizer produced still smells and does not dry out. The problem that partners face in the marketing field is the small number of compost orders. To overcome this problem, the service team has provided appropriate technology as a Simosti tool. The system is equipped with an NPK sensor so that farmers can know the compost quality produced in real-time through Android. Thus, farmers can take appropriate and fast action to produce compost according to standards. The service team has provided training on the use of digital-based marketing applications. The results obtained from this activity are that there has been an improvement in the quality of compost fertilizer processing results that meet the standard NPK levels. Then, there has been an increase in compost fertilizer sales from the sales level before the PKM giant